Windows® 2000 Network Infrastructure Exam Cram™ 2 (Exam 70-216) - Huggins, Diana (Que, 2011)
This exam - one of four MCSE 2000 core exams - measures the ability to install, manage, monitor, configure, and troubleshoot DNS, DHCP, Remote Access, network protocols, IP routing, and WINS in a Windows 2000 network. This book is not intended to teach new material. Instead it assumes that you have a solid foundation of knowledge but can use a refresher on important concepts as well as a guide to exam topics and objectives. This book focuses exactly on what you need to pass the exam - it features test-taking strategies, time-saving study tips, and a special Cram Sheet that includes tips, acronyms, and memory joggers not available anywhere else. The series is supported online at several Web sites: examcram.com, informit.com, and cramsession.com.